THEORETICAL BASICS OF THE GROUND ENAMELS SYNTHESIS WITH REGARD TO PATTERNS OF DIAGONAL LINES AND VERTICAL HOMOLOGY ELEMENTS - Bolshakov, V. I.; Savin, Yu. L.; Prykhodko, O. P.; Fedorchenko, Yu. M.; Savin, L. S.; Savin, Ye. Yu. (Science and Transport Progress, 2008)
In the article theoretical bases of the syntheses of glass-enamel coming from modern concepts of physicochemistry are considered. The main attention is paid to the regularities related to position of anion parts of compounds. In this context the diagonal analogy and vertical homology play the most important role in producing the glass-enamel compositions.